COVID‐19 pandemic and allergen immunotherapy—an EAACI survey. Issue 11 (25th August 2021) - Pfaar, Oliver; Agache, Ioana; Bonini, Matteo; Brough, Helen Annaruth; Chivato, Tomás; Del Giacco, Stefano R.; Gawlik, Radoslaw; Gelincik, Aslı; Hoffmann‐Sommergruber, Karin; Jutel, Marek; Klimek, Ludger; Knol, Edward F.; et al.
Abstract: Background: As in many fields of medical care, the coronavirus disease 2019 (COVID‐19) resulted in an increased uncertainty regarding the safety of allergen immunotherapy (AIT). Therefore, the European Academy of Allergy and Clinical Immunology (EAACI) aimed to analyze the situation in different countries and to systematically collect all information available regarding tolerability and possible amendments in daily practice of sublingual AIT (SLIT), subcutaneous AIT (SCIT) for inhalant allergies and venom AIT. Methods: Under the framework of the EAACI, a panel of experts in the field of AIT coordinated by the Immunotherapy Interest Group set‐up a web‐based retrospective survey (SurveyMonkey ® ) including 27 standardized questions on practical and safety aspects on AIT in worldwide clinical routine. Results: 417 respondents providing AIT to their patients in daily routine answered the survey. For patients (without any current symptoms to suspect COVID‐19), 60% of the respondents informed of not having initiated SCIT (40% venom AIT, 35% SLIT) whereas for the maintenance phase of AIT, SCIT was performed by 75% of the respondents (74% venom AIT, 89% SLIT). No tolerability concern arises from this preliminary analysis. 16 physicians reported having performed AIT despite (early) symptoms of COVID‐19 and/or a positive test result for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Conclusions: This first international retrospective survey in atopic diseases investigated practical aspects and tolerability of AIT during the COVID‐19 pandemic and gave no concerns regarding reduced tolerability under real‐life circumstances. However, the data indicate an undertreatment of AIT, which may be temporary, but could have a long‐lasting negative impact on the clinical care of allergic patients. Abstract : This is the first report of an international retrospective survey in atopic diseases investigating practical aspects and tolerability of AIT during the COVID‐19 pandemic. For patients (without any current symptoms to suspect COVID‐19), 60% of the respondents informed of not having initiated SCIT, 35% SLIT, and 40% venom AIT in the induction phase of AIT though planned. For the maintenance phase of AIT, SCIT was performed by 75%, SLIT by 89%, and venom AIT by 74% of the respondents as regularly planned. Data indicate a (temporary) undertreatment of AIT, but gave no concerns regarding reduced tolerability under real‐life circumstances. Abbreviations: AIT, allergen immunotherapy; COVID‐19, Coronavirus disease 2019; SCIT, subcutaneous Immunotherapy; SLIT, sublingual Immunotherapy; VIT, venom immunotherapy.